STANDARISASI STATUS KONDISI FISIK ATLET CABOR PERORANGAN KONI DAERAH ISTIMEWA YOGYAKARTA - Agung Nugroho, A.M. (Jorpres (Jurnal Olahraga Prestasi), 2016)
This study aims to create a Physical Condition Standards Status Individuals KONI Sports Athletes BranchYogyakarta.This research is a descriptive study with the percentage of test and measurement techniques in data collectionThe population is Puslatda Pre PON DIY athlete in 2010-2011 Phase I and II totaling 142 people . The technique of sampling with purposive sampling is sampling technique with specific criteria or considerations . Criteria samples used in this study are : ( 1 ) athletes entered in the KONI Puslatda DIY individual sports athletes , ( 2 ) follow the good health and physical test phase 1 and phase 2 , ( 3 ) the condition was not injured athletes. Research instrument using test and measurement program Prima KONI Physical Test Center. Analysis of the data in the study is descriptive statistics by finding the scale scores , cumulative frequency and preparation of raw scores using the mean and standard deviations.The results of this study are composed of raw scores of athletes Puslatda Pre PON KONI DIY as follows: ( 1 ) VO 2 max . male and female athletes ; ( 2 ) Push Up athletes male and female , (3 ) Sit Up athletes boys and girls ; ( 4 ) The rate of reaction ( audio and visual ) male and female athletes : ( 5 ) Agility  athletes son and daughter ; ( 6 ) male and female athletes flexibility , and ( 7 ) The balance of male and female athletes ; ( 8 ) The strength of the back muscles male and female athletes ; ( 9 ) leg muscle strength 49 of male and female athletes ; ( 10 ) The strength of the right and left hand squeezing athletes sons and daughters ; (11 ) The strength of the back muscles male and female athletes ; ( 12 ) Expanding strength athletes sons and daughters ; ( 13 ) lung volumes and athletes son and daughter ( 14 ) Power leg male and female athletes . Keywords Status , Physical Condition, Athletes